Incidence of pregnancy loss and characterization of fetal development in red pandas - Jenna Lowe (Bioscientifica, 2021)
Previous reports indicate that red pandas (Ailurus fulgens styani) may experience fetal loss during gestation; however, neither the rate nor timing of pregnancy failure has been described in this species. The objective of this study was to utilize ultrasound video and images collected between 2010 and 2020 at the Cincinnati Zoo and Botanical Garden to better characterize pregnancy loss and fetal development. Trans-abdominal ultrasound examinations were performed on six female red pandas over a 10-year period, resulting in 12 profiles. Pregnancy was diagnosed via ultrasound in 10 of 12 profiles, and 40.0% of pregnancies showed evidence of fetal loss prior to parturition. Pregnancy loss was classified into lost (2 of 10; 20.0%), in which no cubs were produced, or partial loss (2 of 10; 20.0%), in which two concepti were visualized via ultrasound, but only one cub was born. Fetal loss occurred between days 51 and 23 pre-partum. Fetal growth characteristics were documented, including skeletal ossification (occurring between days 32 and 27 pre-partum), crown-rump length, head length, cranial length, and fetal heart rate (173–206 b.p.m.). These findings provide novel insights into pregnancy loss, may serve as a reference for milestones of fetal development, and may be useful in diagnosing pregnancy and assessing pregnancy loss in red pandas.